Sex-specific aspects of endogenous retroviral insertion and deletion. - Gemmell, P; Hein, J; Katzourakis, A (BioMed Central, 2013)
BACKGROUND: We wish to understand how sex and recombination affect endogenous retroviral insertion and deletion. While theory suggests that the risk of ectopic recombination will limit the accumulation of repetitive DNA in areas of high meiotic recombination, the experimental evidence so far has been inconsistent. Under the assumption of neutrality, we examine the genomes of eighteen species of animal in order to compute the ratio of solo-LTRs that derive from insertions occurring down the male germ line as opposed to the female one (male bias). We also extend the simple idea of comparing autosome to allosome in order to predict the ratio of full-length proviruses we would expect to see under conditions of recombination linked deletion or otherwise. RESULTS: Using our model, we predict the ratio of allosomal to autosomal full-length proviruses to lie between32 and 23 under increasing male bias in mammals and between 1 and 2 under increasing male bias in birds. In contrast to our expectations, we find that a pattern of male bias is not universal across species and that there is a frequent overabundance of full-length proviruses on the allosome beyond the ratios predicted by our model. CONCLUSIONS: We use our data as a whole to argue that full-length proviruses should be treated as deleterious mutations or as effectively neutral mutations whose persistence in a full-length state is linked to the rate of meiotic recombination and whose origin is not universally male biased. These conclusions suggest that retroviral insertions on the allosome may be more prolific and that it might be possible to identify mechanisms of replication that are enhanced in the female sex.